Alveolar macrophages protect mice from MERS-CoV-induced pneumonia and severe disease. Issue 4 (July 2022) - Channappanavar, Rudragouda; Selvaraj, Muneeswaran; More, Sunil; Perlman, Stanley
Emerging and re-emerging human coronaviruses (hCoVs) cause severe respiratory illness in humans, but the basis for lethal pneumonia in these diseases is not well understood. Alveolar macrophages (AMs) are key orchestrators of host antiviral defense and tissue tolerance during a variety of respiratory infections, and AM dysfunction is associated with severe COVID-19. In this study, using a mouse model of Middle East respiratory syndrome coronavirus (MERS-CoV) infection, we examined the role of AMs in MERS pathogenesis. Our results show that depletion of AMs using clodronate (CL) liposomes significantly increased morbidity and mortality in human dipeptidyl peptidase 4 knock-in (hDPP4-KI) mice. Detailed examination of control and AM-depleted lungs at different days postinfection revealed increased neutrophil activity but a significantly reduced MERS-CoV-specific CD4 T-cell response in AM-deficient lungs during later stages of infection. Furthermore, enhanced MERS severity in AM-depleted mice correlated with lung inflammation and lesions. Collectively, these data demonstrate that AMs are critical for the development of an optimal virus-specific T-cell response and controlling excessive inflammation during MERS-CoV infection.